2002
DOI: 10.1046/j.1365-2044.2002.02707.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation effects of in vitro serial haemodilution with a balanced electrolyte hetastarch solution compared with a saline‐based hetastarch solution and lactated Ringer's solution*

Abstract: SummaryThe hydroxyethyl starches are a group of compounds that has been associated with impairment of coagulation when large volumes are administered. The thrombelastographÒ is commonly used to assess point-of-care whole blood coagulation. Little is known about the dose-response relationships of haemodilution, and it is reasonable to assume that a linear association exists. This may not be the case with altered electrolyte compositions of the fluids used for haemodilution. We have therefore conducted an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 20 publications
0
46
1
1
Order By: Relevance
“…[102][103][104][105] This TEG pattern is compatible with hemodilutional coagulopathy and platelet dysfunction. 106 Recently, a comparison of the in vivo effect of high, middle and low-MW HES solutions on TEG variables showed prolongation of reaction time with HES 450/0.7/4.6 and deterioration of platelet function with HES 450/0.7/4.6 and HES 70/0.5/4.…”
Section: Coagulation and Hes Solutionsmentioning
confidence: 69%
“…[102][103][104][105] This TEG pattern is compatible with hemodilutional coagulopathy and platelet dysfunction. 106 Recently, a comparison of the in vivo effect of high, middle and low-MW HES solutions on TEG variables showed prolongation of reaction time with HES 450/0.7/4.6 and deterioration of platelet function with HES 450/0.7/4.6 and HES 70/0.5/4.…”
Section: Coagulation and Hes Solutionsmentioning
confidence: 69%
“…Interestingly, this type of biphasic coagulation activity is rarely observed in in vivo studies even at mild haemodilution with HES solutions [22]. Less deterioration of thromboelastography in the high MW group might be due to balanced-salt medium containing Ca 2+ [23]. High MW and high DS HES molecules require more time to be hydrolysed by amylase into smaller molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al [14] reported that a bhHES is not associated with any significant changes in the coagulation profile compared with its saline-based counterpart, which showed hypocoagulation. Moreover, Roche et al [23] asserted that the bhHES enhanced coagulation at 20-40% haemodilution, whereas the saline-based counterpart did not show this initial increase of coagulability. It can therefore be deduced that the lesser deterioration of thromboelastography in the high MW group might be ascribed to the balanced salt-medium, although they compared the same high MW and high DS HES solutions with or without balanced-salt medium.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the effect of CSF on whole blood, we only concentrated on a dilution of up to 30%. From previous work by Roche et al, with lactated Ringer's solution, a procoagulant effect was seen with up to 40% dilution, yet further dilution resulted in a reduction in coagulation [28]. This may suggest that as large a volume of blood as possible (20 ml) should be injected, as even if the CSF leak is small (up to 10 ml), this may represent up to a maximum of 30% haemodilution, allowing for uniform distribution of CSF.…”
Section: Discussionmentioning
confidence: 99%